2004
DOI: 10.1177/154405910408300105
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Esterase Activity and Its Association with the Biodegradation of Dental Composites

Abstract: Pseudocholinesterase (PCE) and cholesterol esterase (CE) can hydrolyze bisphenylglycidyl dimethacrylate (bisGMA) and triethylene glycol dimethacrylate (TEGDMA) monomers. This study will test the hypothesis that enzyme activities showing CE and PCE character are found in human saliva at levels sufficient to hydrolyze ester-containing composites important to restorative denstistry. The study also seeks to ask if the active sites of CE and PCE with respect to composite could be inhibited. Photo-polymerized model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
160
0
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 197 publications
(178 citation statements)
references
References 28 publications
5
160
0
9
Order By: Relevance
“…On the other hand, the elution of monomers from PMMA prosthesis 9,10) is the only study topic concerned with biological factors, such as salivary enzymes and oral microbiota. Composite resins are only dental polymers, which have been studies about oral biodeterioration and reported that the main chain (Bis-GMA) and its modified chain of composite resin polymers were broken down by cholesterol esterases contained in saliva [11][12][13][14][15][16] . Although dentists often notice biodeterioration of PMMA in clinics, through their experience of denture remanufacturing due to discoloration and increased fragility, there has been no scientific study about the biodeteriolation of PMMA.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the elution of monomers from PMMA prosthesis 9,10) is the only study topic concerned with biological factors, such as salivary enzymes and oral microbiota. Composite resins are only dental polymers, which have been studies about oral biodeterioration and reported that the main chain (Bis-GMA) and its modified chain of composite resin polymers were broken down by cholesterol esterases contained in saliva [11][12][13][14][15][16] . Although dentists often notice biodeterioration of PMMA in clinics, through their experience of denture remanufacturing due to discoloration and increased fragility, there has been no scientific study about the biodeteriolation of PMMA.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the fluorine-content from F3 to F6 was also not found to significantly (p > 0.05) alter the hydrolysis rate of the monomers in solution (Figure 3), although select combinations of fluoro and dihydroxyl spacers did yield up to two-times lower degradation rates than the commercial BisGMA. Two of the more stable monomers were also examined for their relative stability towards CE (Figure 4), which is an enzyme-like activity that has been found in saliva to be highly active towards the commercial monomer BisGMA [2,4]. Within 24 h of exposure to CE, BisGMA had undergone degradation by 79% and produced equivalent molar amounts of bisphenol A bis (2,3-dihydroxypropyl) ether (BisHPPP), the terminal degradation by-product.…”
Section: Resultsmentioning
confidence: 99%
“…The elevated advancing values (79° to 86°) after incubation with albumin indicates that the hydrophobic fluorine groups are likely still present and influencing the surface after exposure to albumin, therefore maintaining the hydrophobic surface chemistry that was incorporated to enhance the stability against hydrolysis. Two of the more stable monomers were also examined for their relative stability towards CE (Figure 4), which is an enzyme-like activity that has been found in saliva to be highly active towards the commercial monomer BisGMA [2,4]. Within 24 h of exposure to CE, BisGMA had undergone degradation by 79% and produced equivalent molar amounts of bisphenol A bis (2,3-dihydroxypropyl) ether (BisHPPP), the terminal degradation by-product.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations